2016
DOI: 10.1097/rlu.0000000000001370
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in Cutaneous Melanoma

Abstract: Melanoma is an important public health problem, and its incidence is increasing worldwide. The disease status of regional lymph nodes is the most important prognostic factor in early-stage melanoma patients. Sentinel lymph node biopsy (SLNB) was introduced in the early 1990s as a less invasive procedure than complete lymph node dissection to allow histopathologic evaluation of the "sentinel lymph node" (SLN), which is the first node along the lymphatic pathway from a primary tumor. Sentinel lymph node biopsy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…A higher DR and the larger number of SLNs identified by the SPECT/CT on a head-to-head comparison with PL can theoretically also determine a meaningful impact in surgical decision making. Nevertheless, the preoperative use of SPECT/CT for the identification of SLNs is not only important for the additional number of SLNs but also for the capability of providing anatomical information [21,53]. Furthermore, SPECT/CT may also localize unspecific hot spots that could be mistaken as additional SLNs using only PL [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher DR and the larger number of SLNs identified by the SPECT/CT on a head-to-head comparison with PL can theoretically also determine a meaningful impact in surgical decision making. Nevertheless, the preoperative use of SPECT/CT for the identification of SLNs is not only important for the additional number of SLNs but also for the capability of providing anatomical information [21,53]. Furthermore, SPECT/CT may also localize unspecific hot spots that could be mistaken as additional SLNs using only PL [54].…”
Section: Discussionmentioning
confidence: 99%
“…SPECT/CT seems to provide a meaningful impact on surgery, possibly influencing the patient outcome [53]. The large prospective multicenter International Atomic Energy Agency Sentinel Node Trial demonstrated that SPECT/CT had modified the surgical approach in 97 patients with melanoma (37% of the patient population): 41.6%, 39.7%, 33.3% and 30.2% of subjects with head and neck, trunk, lower limb and upper limb lesions, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the SLN avoids the side effects of complete lymph node dissection (CLND); furthermore, prospective trials demonstrated no improvement in survival for patients with melanoma undergoing CLND [ 6 , 7 ]. CLND should, therefore, be preferentially suggested for patients with positive SLN [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel lymph node biopsy (SLNB) is a well-established technique used in many subsites of oncology, including breast cancer, skin cancer and melanoma. In these settings, SLNB has been shown to be sensitive, specific, reduce morbidity and demonstrates survival rates at least as good as with more comprehensive lymph node dissection [ 4 , 5 ]. The most recent National Comprehensive Cancer Network (NCCN) clinical practice guidelines for head and neck oncology and National Institute for Clinical Excellence (NICE) guidelines addresses the clinical dilemma of the N0 neck in early stage (T1/T2) oral cancer, stating that sentinel lymph node biopsy is an alternative to elective neck dissection for identifying occult cervical metastasis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%